Stereoselective Synthesis of γ‐Butyrolactones Subunit of Polycavernoside A. (3rd July 2018) - Kadari, Sudhakar; Yerrabelly, Hemasri; Gogula, Thirupathi; Erukala, Yadaiah Goud; Yerrabelly, Jayaprakash Rao; Begari, Prem Kumar
Abstract : An efficient and versatile linear synthesis of γ‐butyrolactone subunit of polycavernolide A has been reported in 14.2% overall yield with 10 linear steps by employing Sharpless asymmetric epoxidation, ring‐closing metathesis, and diastereoface selective hydrogenation. Abstract :